2004
DOI: 10.1007/s00216-004-2490-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic polymers adsorbing bisphenol�A and its analogues prepared by covalent molecular imprinting using bisphenol�A dimethacrylate as a template molecule

Abstract: Synthetic polymers which can adsorb bisphenol A (BPA) and related compounds were prepared by a covalent molecular imprinting technique. BPA dimethacrylate, used as template molecule, was polymerized with a crosslinker, triethylene glycol dimethacrylate (TEGDMA) or trimethylol propane trimethacrylate (TRIM). After the polymerization treatment with dilute NaOH was used to cleave BPA from the polymers. For high recovery of BPA with low polymer matrix degradation, the hydrolysis conditions were determined to be tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Refs. [5][6][7][8][9][10]). Comparatively few reports describe imprinting inorganic materials [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [5][6][7][8][9][10]). Comparatively few reports describe imprinting inorganic materials [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Molecularly imprinted polymers for phenolic compounds (bisphenols, alkylphenols and their derivatives) are usually obtained by non-covalent imprinting techniques [34-41, 82, 85, 86], while in the literature there are only a few reports about covalent or semi-covalent imprinting [39,[87][88][89]. The latter two techniques require the use of harsh conditions in order to remove target compounds which consequently can result in the partial degradation of the polymer matrix.…”
Section: Molecularly Imprinted Polymers (Mips)mentioning
confidence: 99%
“…2) was investigated by measuring their retention on imprinted polymers with a mobile phase of chloroform/acetonitrile (9:1 (v/v)). Because previously reported BPA-imprinted polymers exhibited high affinities for BPA and its structural analogue compounds, [14][15][16] we employed this condition. The results are shown in Fig.…”
Section: Binding Affinity Of the Imprinted Polymersmentioning
confidence: 99%
“…Due to such characteristics, many research groups reported BPA-imprinted polymers prepared using various templates. [11][12][13][14][15][16] We report herein a BPA binding imprinted polymer that has been prepared by immobilization of the template, 4,4′-bis(4-hydroxyphenyl)valeric acid, to a silica matrix. This yielded imprinted polymers of uniform size and shape with structurally controlled binding sites.…”
Section: Introductionmentioning
confidence: 99%